Diversity of aphantasia revealed by multiple assessments of visual imagery, multisensory imagery, and cognitive style - Takahashi, Junichi; Saito, Godai; Omura, Kazufumi; Yasunaga, Daichi; Sugimura, Shinichiro; Sakamoto, Shuichi; Horikawa, Tomoyasu; Gyoba, Jiro (Frontiers in Psychology, 2023)
Aphantasia-a condition wherein individuals have a reduced or absent construction of voluntary visual imagery-is diagnosed using either the Vividness of Visual Imagery Questionnaire (VVIQ) or self-identification. However, a significant discrepancy exists between the proportions of aphantasia in the populations assessed using these two criteria. It is unclear why the reported proportions differ excessively and what percentage of people cannot form visual imagery. We investigated the replicability of the proportion of people with aphantasia using both criteria in the same population of participants. Therefore, we explored the potential causes of the discrepancy and characteristics of putative aphantasia in terms of multisensory imagery, cognitive style, and face recognition ability. First, we conducted an online sampling study (Study 1: N = 2,871) using the VVIQ, selfidentification of a reduction in visual imagery, Questionnaire upon Mental Imagery (QMI), and Verbalizer-Visualizer Questionnaire (VVQ). We found that 3.7% and 12.1% fulfilled the VVIQ and self-identification criteria, respectively, roughly replicating the proportions reported in previous studies. The self-identification criterion-but not the VVIQ criterion-contains items related to face recognition; hence, we suspected that face recognition ability was factor contributing to this discrepancy and conducted another online sampling study (Study 2: N = 774). We found a significant correlation between VVIQ and face recognition ability in the control group with self-identification, but not in the group defined by low VVIQ (VVIQ ≤ 32). As the participants in the control group with 2 This is a provisional file, not the final typeset article self-identification tended to exhibit moderately high VVIQ scores but low face recognition ability, we reason that the discrepancy can be partially explained by the contamination of individual differences in face recognition ability. Additional analyses of Study 1 revealed that the aphantasia group included participants who lacked all types of sensory imagery or only visual imagery in multisensory imagery and exhibited a non-specific cognitive style. This study indicates that the VVIQ alone may be insufficient to diagnose individuals who report an inability to form visual imagery. Furthermore, we highlight the importance of multiple assessments-along with the VVIQ-to better understand the diversity of imagery in aphantasia.